Systematic review with meta‐analysis: neuroimaging in hepatitis C chronic infection. Issue 9 (14th March 2018) - Oriolo, G.; Egmond, E.; Mariño, Z.; Cavero, M.; Navines, R.; Zamarrenho, L.; Solà, R.; Pujol, J.; Bargallo, N.; Forns, X.; Martin‐Santos, R.
Summary: Background: Chronic hepatitis C is considered a systemic disease because of extra‐hepatic manifestations. Neuroimaging has been employed in hepatitis C virus‐infected patients to find in vivo evidence of central nervous system alterations. Aims: Systematic review and meta‐analysis of neuroimaging research in chronic hepatitis C treatment naive patients, or patients previously treated without sustained viral response, to study structural and functional brain impact of hepatitis C. Methods: Using PRISMA guidelines a database search was conducted from inception up until 1 May 2017 for peer‐reviewed studies on structural or functional neuroimaging assessment of chronic hepatitis C patients without cirrhosis or encephalopathy, with control group. Meta‐analyses were performed when possible. Results: The final sample comprised 25 studies (magnetic resonance spectroscopy [N = 12], perfusion weighted imaging [N = 1], positron emission tomography [N = 3], single‐photon emission computed tomography [N = 4], functional connectivity in resting state [N = 1], diffusion tensor imaging [N = 2] and structural magnetic resonance imaging [N = 2]). The whole sample was of 509 chronic hepatitis C patients, with an average age of 41.5 years old and mild liver disease. A meta‐analysis of magnetic resonance spectroscopy studies showed increased levels of choline/creatine ratio (mean difference [MD] 0.12, 95% confidence interval [CI] 0.06‐0.18), creatine (MD 0.85, 95% CI 0.42‐1.27) and glutamate plus glutamine (MD 1.67, 95% CI 0.39‐2.96) in basal ganglia and increased levels of choline/creatine ratio in centrum semiovale white matter (MD 0.13, 95% CI 0.07‐0.19) in chronic hepatitis C patients compared with healthy controls. Photon emission tomography studies meta‐analyses did not find significant differences in PK11195 binding potential in cortical and subcortical regions of chronic hepatitis C patients compared with controls. Correlations were observed between various neuroimaging alterations and neurocognitive impairment, fatigue and depressive symptoms in some studies. Conclusions: Patients with chronic hepatitis C exhibit cerebral metabolite alterations and structural or functional neuroimaging abnormalities, which sustain the hypothesis of hepatitis C virus involvement in brain disturbances.